A comprehensive study on biological activites of Halimeda copiosa and its insilico analysis (Applied Biological Research, 2024)
The Halimeda extracts were obtained using two different solvents: methanol and ethyl acetate whereas, high amount of phytochemicals were identified in the methanol extract when compared to ethyl acetate. So, the further studies were carried out in methanolic extract. The evaluation of antioxidant activity of methanol extract comprises total antioxidant capacity, DPPH, reducing power assay, hydrogen peroxide and were performed and the IC50 values are 97.26, 872.38, 385.91, 592.02/mg.ml-1 respectively. The algae showed good antimicrobial activity against five organisms. Halimeda copiosa also showed in vitro amylase inhibitory activity with IC50 value of 4.30 / mg.ml-1, in vitro glucosidase inhibition assay with IC50 value of 9.11/ mg.ml-1 and as well as anti- inflammatory activity of IC50 value was 587.5/mg.ml-1. In addition, Bioinformatic studies have also done to the protein ribosomal protein L5, partial (chloroplast) which is present in Halimeda copiosa, have antioxidant activity as well as apoptosis activity. Thus the present study was reported first time which confirms the antioxidant, antimicrobial, antibacterial, antidiabetic and antiinflammatory activities for Halimeda copiosa which was further validated by insilico analysis that can be developed as a potent drug.
Keywords: Halimeda copiosa; antioxidant activity; Antimicrobial activity; Antidiabetic activity; anti-inflammatory; in silico